2020
DOI: 10.1007/s00068-020-01487-x
|View full text |Cite
|
Sign up to set email alerts
|

Recidivism at the puerto rico trauma hospital

Abstract: Purpose Although trauma represents a leading cause of morbidity and mortality worldwide, there is limited and heterogeneous evidence regarding trauma recidivism and its outcomes. This analysis determined the rate and independent risk factors of trauma recidivism and compared the first and second injury episode among recidivists. Methods An IRB-approved retrospective cohort study was performed with data from the Puerto Rico Trauma Hospital Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…However, by asking the patients about prior injury we likely improved our capture of the true trauma recurrence rate; the 49.3% rate of PTI in this study is at the upper end of the previously reported literature. 10,13,14,24,25,32 Last, our follow-up is limited to only 6 months in this study and longer follow-up times could show different results.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, by asking the patients about prior injury we likely improved our capture of the true trauma recurrence rate; the 49.3% rate of PTI in this study is at the upper end of the previously reported literature. 10,13,14,24,25,32 Last, our follow-up is limited to only 6 months in this study and longer follow-up times could show different results.…”
Section: Discussionmentioning
confidence: 90%
“…Trauma surgeons have long recognized the risk of recurrent injury as another component of this chronic disease process, and many studies have shown that a substantial proportion of trauma patients will experience another significant injury 10–14 . Yet, little research has considered the outcomes for patients with recurrent traumatic injury, and the few existing studies focus on acute outcomes such as mortality.…”
mentioning
confidence: 99%
See 3 more Smart Citations